CuAAC in a Distal Pocket: Metal Active‐Template Synthesis of Strapped‐Porphyrin [2]Rotaxanes. Issue 55 (3rd August 2017) - Miyazaki, Yuta; Kahlfuss, Christophe; Ogawa, Ayumu; Matsumoto, Takashi; Wytko, Jennifer A.; Oohora, Koji; Hayashi, Takashi; Weiss, Jean
Abstract: Invited for the cover of this issue are the groups of Takashi Hayashi from Osaka University and Jean Weiss from the CNRS at the Université de Strasbourg. The image depicts this collaboration for the synthesis of rotaxane by a tandem active metal template with strapped porphyrin. Read the full text of the article at 10.1002/chem.201702553 . Abstract : " The friendship is illustrated by the convivial atmosphere that surrounds the science on our plates ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 13579 ff. (DOI:10.1002/chem.201702553 ).